Microscopical analysis of Candida albicans biofilms on heat-polymerised acrylic resin after chlorhexidine gluconate and sodium hypochlorite treatments - Batista da Silva, Paulo Mauricio; Rodriguez Acosta, Emilio Jose T.; Pinto, Luciana de Rezende; Graeff, Marcia; Spolidório, Denise Madalena Palomari [UNESP]; Almeida, Ricardo S.; Porto, Vinicius Carvalho (Wiley-Blackwell, 2011)
The ability of Candida albicans to form biofilms on denture surfaces is a significant cofactor in the pathogenesis of denture stomatitis. In this study, we applied a differential staining approach and scanning electron microscopy (SEM) to analyse the effect of sodium hypochlorite and chlorhexidine gluconate on the viability, removal and morphology of C. albicans forming biofilms on denture acrylic using an in vitro model. Immediately after treatment, to distinguish live from dead C. albicans cells in the remaining biofilms, the specimens were stained differentially and analysed by confocal scanning laser microscopy. Moreover, morphological alterations of fungal cells were investigated using scanning electron microscopy. All disinfectant solutions killed all remaining fungal cells on the specimens. Interestingly, 4% chlorhexidine did not remove these cells from the acrylic resin surface whereas sodium hypochlorite solutions (1% and 2%) provided almost complete biofilm removal. Furthermore, treating the specimens with sodium hypochlorite induced cell morphology alterations, as seen in the residual fungal cells. Finally, according to our findings, it can be suggested that sodium hypochlorite solutions are the first choice as denture cleanser when compared with 4% chlorhexidine because those solutions not only killed C. albicans biofilms but also removed them from the heat-polymerised acrylic resin.
Keywords: Candida albicans; denture stomatitis; biofilm; chlorhexidine gluconate; sodium hypochlorite